Direct and Indirect Influence of HRM Practices on Employee Performance and Turnover Intention (Malaysian Management Journal, 2007)
This study attempted to narrow the dearth in the literature with regard to the influence of human resource management (HRM) practices on employees. The study, using a sample of clerical front liners in service-based cooperatives in West Malaysia revealed that HRM practices (training and development, performance appraisal, communication and participation, and rewards) had a significant direct positive and indirect positive relationship with employee performance. The indirect relationship was mediated by affective organisational commitment. In contrast, HRM practices only had an indirect relationship with turnover intention, mediated by affective organisational commitment. Affective supervisory commitment did not mediate the relationship between HRM practices and employee performance nor the relationship between HRM practices and turnover intention. The results suggested that HRM practices can enhance employee performance directly as well as indirectly, through fostering affective organisational commitment. In addition, HRM practices can reduce turnover intention only indirectly through enhancing affective organisational commitment.